Online vs Konvensional: Keunggulan dan Konflik Antar Moda Transportasi di Kota Makassar - Ahsani Amelia Anwar (Hasanuddin University, 2017)
The existence of online mode of transportation has attracted consumers’ attention, and therefore many switch from the use of conventional to online mode of transportation. The switch has become a trigger of conflict between drivers of conventional transportation, such as city transportation (angkot), taxi, motorbike (bentor), rickshaw (ojek pangkalan), and drivers of online transportation, such as Grab and Go-Jek. This artikel is focused on the existence and the conflict between these two mode of transportations in Kota Makassar. It was found that online transportation has become an alternative of transportation for society for a number of reasons: practicality, transparency, trustworthiness, security, insurance, features, discount and promotion rates, as well as new employment/part-time opportunities. The existence of online-based transportation has caused a conflict between the two. In one side, online transportation is considered to facilitate drivers and their passangers. On the other side, online transportation got criticised from drivers of conventional transportation due to the fact that the latter is being marginalised by the former. Conflict between the two is commonly base on operating lisence, colour of vehicle plate that significantly impacted on payment of taxes, passangers’ recruitment base, and competitive online transportation rates. The rate has becomeone of the advantages of online transportation as well as one of the source of conflicts between conventional and online transportation.